UIN Sunan Kalijaga Student’s Response to Online Briefing on Community Service Programs Using the Zoom Application During the Covid-19 Pandemic - Supriyati, Hikmah; Krisdiyanto, Didik (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to determine how the descriptions and responses of students participating in the KKN (Community Service Programs) debriefing at UIN Sunan Kalijaga Yogyakarta which is done online using the zoom application with youtube streaming. This research is a descriptive study using survey research methods. The research instrument used was a questionnaire distributed online with a google form. The distribution of questionnaires to 2734 students from 8 faculties who took part in the online KKN. In addition, online interviews were also conducted with several students who took part in online KKN. Secondary data collection is done through a literature study to find documents, articles, news, and others. The research data were analyzed using descriptive statistics. Furthermore, the research results are described in the paragraph. The results showed that during the Covid-19 pandemic, the use of the zoom application was an alternative in debriefing KKN online at UIN Sunan Kalijaga Yogyakarta. This is evident from the student response showing that 80.8% of students agree with the statement that the use of the zoom application with youtube streaming is the right solution in debriefing KKN online during the Covid-19 pandemic.